The Kumaraswamy Lindley Regression Model with Application on the Egyptian Stock Exchange: Numerical study,Regression model - Samy Abdelmoezz; Salah M. Mohamed (Jurnal Matematika, Statistika dan Komputasi, 2021)
We introduce and study the Kumaraswamy Lindely Distribution (KLD)  model, which has increasing, decreasing, upside-down bathtub and bathtub shaped hazard functions.. We perform a Monte Carlo simulation study to assess the finite sample behavior of the maximum likelihood estimates of the parameters. We define a new regression model based on the new distribution. The new regression was applied to data from the Egyptian stock exchange in the period of (2015-2019). Finally, we study some properties of regression Residual analysis The martingale residual, Deviance component residual.